(untitled) (Journal of Nepal Physical Society, 2024)
The magnetic reconnection between the Interplanetary Magnetic Field (IMF) and the Earth’s magnetic field is the maindriver of solar energy input to generate geomagnetic storms. In this work, we employ data from the Global Ionospheric Radio Observatory (GIRO) to study the effects of the March and April 2023 geomagnetic storms on ionospheric Total Electron Content (TEC) and F2 layer critical frequency (foF2) over the Jeju Island, South Korea. We investigate the possible ionospheric connection to solar wind parameters through cross-correlation and continuous wavelet transforms (CWT) analyses. Total electron content and foF2 show a positive correlation above 0.9 to solar wind proton density (Nsw) without time-lag during both storms. On the other side, during the storm of March 2023, TEC and foF2 show a negative correlation of 0.8 to the IMF By component with a time-lag of one hour, while the IMF Bz component and the geomagnetic SYM-H index show a negative correlation of 0.85 and 0.95, respectively without time lag. Conversely, during the storm of April 2023, the correlation of the IMF Bx component to TEC and foF2 are positive with a value of 0.7 with a time-lag of 2.4 hours, while the IMF By and Bz components show a negative correlation to SYM-H around 0.9 with absence of time-lag. These results show the significant fluctuations in ionospheric parameters over Jeju Island, South Korea and emphasizes the sensitivity and importance of ionosphere to space weather monitoring for understanding and mitigating the detrimental effects on communication and navigation systems.